The Impact of Scenario Planning and Leadership on Non-Financial Performance in the Multi-Level Marketing (MLM) Industry - Yun Yu Chuan; Teck Khun, Joshua Loo (AIBPM Publisher, 2022)
The purpose of this study was to explore the impact of strategic management and leadership styles on the non-financial performance in Multi-Level Marketing (MLM) companies. This research was carried out in Penang and Kuala Lumpur, using judgmental and snowball sampling methods. A total of 155 valid samples were gathered and the data collected was analysed using Statistical Package for Social Sciences (SPSS) software. Resource-based view theory explains how scenario planning can serve as a resource to the company leading to better non-financial performance. Dynamic capability of leadership is another essential factor for MLM companies to thrive in the marketplace.The findings indicate that macro scenario, micro scenario, and transformational leadership have significant positive impact on non-financial performance, whereas transactional leadership influences non-financial performance negatively. The industry scenario does not have a significant relationship with non-financial performance. These findings assist researchers and management team in the MLM industry to have a better understanding on factors contributing to better non-financial performance.